Синтез математичної моделі тягового електроприводу постійного струму з нелінійними елементами для дослідження аварійних режимів - Михаліченко, Павло Євгенович; Маркова, Євгенія Юхимівна; Марков, Михайло; Mikhalichenko, Pavlo; Markova, Yevheniia; Markov, Mykhailo (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто синтез математичної моделі тягового електроприводу постійного струму з урахуванням нелінійних елементів для дослідження аварійних режимів системи електричної тяги. Обґрунтовано необхідність врахування магнітної нелінійності, вихрових струмів та температурної залежності параметрів при аналізі електромагнітних перехідних процесів. Запропоновано еквівалентну схему заміщення з додатковим короткозамкненим контуром, що моделює дію вихрових струмів. Проаналізовано умови виникнення генераторного режиму при порушенні балансу між напругою живлення та внутрішньою ЕРС. Встановлено вплив швидкості зміни напруги та параметрів магнітної системи на характер перехідних процесів. Отримані результати можуть бути використані для підвищення точності моделювання аварійних режимів та вдосконалення систем захисту тягових електроприводів. /// EN: The paper addresses the synthesis of a mathematical model of a DC traction electric drive with nonlinear elements for the investigation of emergency operating modes in electric traction systems. The necessity of considering magnetic nonlinearity, eddy current effects, temperature dependence of winding parameters, and nonlinear magnetization characteristics in the analysis of electromagnetic transient processes is substantiated. An equivalent circuit of the traction motor is proposed, including a short-circuited loop representing eddy current effects, and the parameters of the traction power circuit are synthesized for different motor connection schemes. The mechanisms of generator current occurrence under short-circuit conditions and sudden voltage fluctuations in the traction network are analyzed. The conditions under which the electric drive switches to a generator mode due to imbalance between supply voltage and the resultant generated EMF are determined. It is shown that the rate of supply voltage change and magnetic system parameters significantly influence the nature and amplitude of transient processes. The obtained results can be applied to improve the accuracy of mathematical modeling of emergency modes, enhance protection systems of traction power circuits, and increase the operational reliability and energy safety of DC traction networks.
Synthesis of a mathematical model of a direct current traction drive with nonlinear elements for the study of emergency modes
Keywords: електропривод постійного струму; нелінійність; математична модель; перехідні процеси; аварійний режим; генераторний струм; коротке замикання; магнітна характеристика; еквівалентна схема заміщення; електромагнітні процеси; DC electric drive; traction motor; nonlinearity; mathematical model; transient processes; emergency mode; generator current; short circuit; magnetization characteristic; eddy currents; equivalent circuit; electromagnetic processes; stability